EFFECT OF PROCESSING OPERATIONS OF CAKES ON AFLATOXINS CONTENTS - Salah O. Ahmed (Mesopotamia Journal of Agriculture)
The aim of this study was to investigate the effect of different food processing operations including chemical and physical methods of cakes on the presence of added aflatoxins B1, B2, G1 and G2. Different concentrations of baking powder were added to the dough of the cake treatments. The dough of cake was ripenned in the conventional oven or in the microwaves oven or using both ovens successively. Aflatoxins concentrations were determined. Results demonstrated That significant (P<0.05) reduction of all aflatoxins contents was shown in the manufacturing of the cakes, in which 29.8-100, 31.3-100, 55.6-100 and 32.9-100% of aflatoxins B1, B2, G1 and G2 were reduced, respectively. Addition of 1% of baking powder to the cakes dough resulted in more reduction in all aflatoxins among the treatments and also in case of reduction index. Results also show that ripening of the cakes dough in microwaves oven and both conventional and microwaves ovens reduced all aflatoxins more than others using the conventional oven.